2020
DOI: 10.1002/jcla.23503
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of low cut‐off index values of Elecsys® HIV combi PT assay in predicting false‐positive results

Abstract: HIV/AIDS continues to pose a serious burden of morbidity and mortality globally. As reported by WHO, till 2018, there were more than 37.9 million people living with HIV and only 75% of them were aware of their infection status. 1 The spread of HIV/AIDS is alarming to many countries, including China, where the HIV prevalence is <0.1%. 2 In recent years, China has strengthened advocating to improve public awareness of HIV/AIDS. The implementation has gone all out to achieve the UNAIDS/WHO 90-90-90 target, namely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…In this study, we conducted a retrospective analysis of HIV screening test results in a large hospital and found that the screening positive rate in the Xiamen region of China was approximately 0.28%. The FPR was 43.4% (199/459), and it was high and similar to other reports studying HIV screening and low prevalence settings [ 15 , 16 ]. Some researches focused on assessing the role of the S/CO ratio in reducing the frequency of false-positive results [ [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we conducted a retrospective analysis of HIV screening test results in a large hospital and found that the screening positive rate in the Xiamen region of China was approximately 0.28%. The FPR was 43.4% (199/459), and it was high and similar to other reports studying HIV screening and low prevalence settings [ 15 , 16 ]. Some researches focused on assessing the role of the S/CO ratio in reducing the frequency of false-positive results [ [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 89%
“…1 (panel B) shows a flow diagram of the HIV testing in the retrospective study. Similar to syphilis antibodies, multiple studies have shown an association of the S/CO value of HIV screening tests with subsequent verification of HIV diagnosis using confirmatory testing and clinical information [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Confirmation testing commonly used in the United States and some other countries includes antibody differentiation assays (in the present study was the Bio-Rad Geenius assay) and HIV RNA PCR.…”
Section: Data Descriptionmentioning
confidence: 99%